2015
DOI: 10.1039/c5cp00931f
|View full text |Cite
|
Sign up to set email alerts
|

Sequestering uranium from UO2(CO3)34−in seawater with amine ligands: density functional theory calculations

Abstract: The polystyrene-supported primary amine -CH2NH2 has shown an at least 3-fold increase in uranyl capacity compared to a diamidoxime ligand on a polystyrene support. This study aims to understand the coordination of substitution complexes from UO2(CO3)3(4-) and amines using density functional theory calculations. Four kinds of amines (diethylamine (DEA), ethylenediamine (EDA), diethylenetriamine (DETA) and triethylenetetramine (TETA)) were selected because they belong to different classes and have different chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Although a number of other uranium extraction methods have been investigated, amidoxime (AO)-based adsorbents are recognized by many groups as the most promising material. Under the memorandum of understanding between the Chinese Academy of Science (CAS) and the U.S. Department of Energy (DOE), the research groups in SINAP and ORNL parallel-developed and compared several adsorbents based on AO groups. Nevertheless, real ocean adsorption experiments must still be further promoted.…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of other uranium extraction methods have been investigated, amidoxime (AO)-based adsorbents are recognized by many groups as the most promising material. Under the memorandum of understanding between the Chinese Academy of Science (CAS) and the U.S. Department of Energy (DOE), the research groups in SINAP and ORNL parallel-developed and compared several adsorbents based on AO groups. Nevertheless, real ocean adsorption experiments must still be further promoted.…”
Section: Introductionmentioning
confidence: 99%
“…45 Although the most stable binding modes (η 2 for NAO and GDO, tridentate for GIO) may be disrupted upon dehydration, the residual amine groups may account for the binding with uranyl. 46 For the [UO 2 (L − H)] + complexes, unique fragmentation pathways were observed, depending on the structures of the ligands themselves. For the NAO ligand, two fragment ions at m/z of 453 and 427 were observed (Fig.…”
Section: The Fragmentation Pathway Of Uranyl Complexes In Cidmentioning
confidence: 99%
“…At present, theoretical calculations are essential for designing efficient adsorption groups for extracting uranium from seawater. Previous studies , showed that the alkyl-substituted amidoximes (Figure a) increase the selectivity for uranyl ions, and the ortho position amino to the amidoxime group can enhance the extraction ability of uranyl. These results raise the question of whether introduction of an ortho position amino group of the alkyl-substituted amidoxime can enhance its selectivity to uranyl.…”
Section: Introductionmentioning
confidence: 99%